Use of Genetic Algorithms in Economic Decision Making Processes - Novotná, Veronika; Luhan, Jan; Budík, Jan (Česká společnost pro systémovou integraci, 2011)
The article deals with the use of genetic algorithms in economic decision-making processes and focuses on the system of designing an investment portfolio. The application part shows a case study in which an investment portfolio is designed focusing on intraday speculations on the world currency market. The solution to the case study used the MatLab system enhanced by financial toolboxes. The conclusion summarizes the methods used for the realization of the case study in general.

The article deals with the use of genetic algorithms in economic decision-making processes and focuses on the system of designing an investment portfolio. The application part shows a case study in which an investment portfolio is designed focusing on intraday speculations on the world currency market. The solution to the case study used the MatLab system enhanced by financial toolboxes. The conclusion summarizes the methods used for the realization of the case study in general.
Use of Genetic Algorithms in Economic Decision Making Processes
Keywords: Genetic algorithms; decision-making system; decision-making process; information system; MatLab; investment portfolio; Genetic algorithms; decision-making system; decision-making process; information system; MatLab; investment portfolio